Optimization of the cultivation of donor mesenchymal stromal cells for clinical use in cellular therapy - Valim, Vanessa de Souza (2014)
Mesenchymal stromal cells (MSC) have shown their benefits in graft-versus-host disease (GVHD), with five unsettled matters: 1) MSCs expansion in medium with Fetal Bovine Serum (FBS) and its risk of xenoreaction; 2) The number of cells indicated for therapy that is relatively high, with the need to optimize the expansion, number and time wise; 3) The utilization of third party donors; 4) Culture passage number (P); and 5) Source of the cells. This study was designed to determine the superiority of the Platelet Lysates (PL) over FBS on the expansion of MSC, the optimal cell’ plating density and days between each pass, and to investigate if donor total nucleated cells (TNC) obtained from the washouts of discharged bags and filters of hematopoietic stem cell transplantation (HSCT) can be expanded to be used at clinical grade. TNC were removed, plated and after the first passage were cultivated in different concentrations with FBS or PL, and the number of days to reach 80% of confluence was observed. Next, cultures with the same plating density were fed either with PL or with FBS and after seven days counted to analyze how much they had grown in that period. The proliferation of mesenchymal stromal cells in the presence of PL and SFB was averaged 11.88 and 2.5 times, respectively, in a period of 7 days. The highest concentration of plating cells using PL took less time to reach confluence as compared with the three lower ones. This study suggests that the PL is the best choice as a supplement to expand MSC and to allow the proliferation of enough number of MSC at P2 for clinical use.